Effect of second phase particle on fatigue crack growth behavior in microstructure controlled steels - Mustapa, Mohammad Sukri (2010)
A series of AK-constant fatigue crack growth tests in Paris regime were carried out to investigate the effect of second phase particle on fatigue crack growth behavior of microstructure controlled steels with uniformly distributed hard particles. Three kinds of materials were used in this study, ferrite matrix with pearlite particles (FP), ferrite matrix with bainite particles (FB) and ferrite matrix with martensite particles (FM). The fatigue crack growth tests by using a single edge cracked tension (SECT) type specimen was performed inside a scanning electron microscope chamber equipped with a servo-hydraulic fatigue machine. The results showed that the fatigue crack growth rates for all materials did not coincide with each other, even when the crack growth curves were arranged by the effective stress intensity factor range. From the in-situ observations, crack tip stress shielding phenomena, such as interlocking, branching, etc. were found on the crack wake, which enhanced fatigue crack growth resistance. In ferrite-pearlite (FP) steel, small size and small spacing of hard particles seemed to induce small but frequent crack deflections, which resulted in crack closure phenomena. On the other hand, large size of pearlite particle seemed to induce stress shielding phenomena and then contribute to high crack growth resistance, which was the main reason for higher fatigue crack growth resistance of the large size and spacing of pearlite particle compared to the small size of pearlite particle. It was similar result for the ferrite-bainite (FB) steel where the large size and large spacing of bainite particles enhanced the fatigue crack growth resistance. The higher volume fraction of hard particle also influenced the fatigue crack growth behavior. In this investigation, the result indicated the higher volume fiaction of hard particle in the ferrite-bainite (FBI) steel has significantly increased the fatigue crack growth resistance compared to the ferrite-bainite (FB2) with lower volume fraction and ferrite-pearlite (FP) steels. The effect of hardness of second phase particle was also investigated. The results revealed that the ferrite-martensite (FM) steel showed significantly higher fatigue crack growth resistance compared to the ferrite-pearlite (FP) and ferrite-bainite (FB) steels. From the in-situ observations, the crack tip stress shielding phenomena, such as interlocking, branching, etc were found on the crack wake, which enhanced fatigue crack growth resistance. In the FM steel, the deformation of plastic constrained at the crack tip in ferrite region seemed to induce stress shielding phenomena and then contribute to high crack growth resistance, which was the main reason for lower fatigue crack growth rate of the FM steel with harden martensite particle compared to the FP and FB steels with soften pearlite and bainite particles. Keywords : Fatigue crack growth behavior, AK-constant fatigue crack growth tests, crack tip stress shielding, interlocking, crack closure, ferrite-pearlite, ferrite-bainite, ferrite-martensite, hardparticle, plastic zone size, plastic constrained deformation.